Crip Negativity - Smilges, J. Logan (Forerunners: Ideas First, 2023)
pImagining anti-ableist liberation beyond the rubrics of access and inclusion In the thirty years since the Americans with Disabilities Act was signed into law, the lives of disabled people have not improved nearly as much as activists and politicians had hoped. In emCrip Negativity/em, J. Logan Smilges shows us what's gone wrong and what we can do to fix it./p pLeveling a strong critique of the category of disability and liberal disability politics, Smilges asks and imagines what horizons might exist for the liberation of those oppressed by ableism-beyond access and inclusion. Inspired by models of negativity in queer studies, Black studies, and crip theory, Smilges proposes that bad crip feelings might help all of us to care gently for one another, even as we demand more from the world than we currently believe to be possible. emForerunners: Ideas First/em is a thought-in-process series of breakthrough digital publications. Written between fresh ideas and finished books, Forerunners draws on scholarly work initiated in notable blogs, social media, conference plenaries, journal articles, and the synergy of academic exchange. This is gray literature publishing: where intense thinking, change, and speculation take place in scholarship./p